1991
DOI: 10.1007/bf00259682
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and transcriptional characterization of a morphological modifier: the Aspergillus nidulans stunted (stuA) gene

Abstract: The functions of at least four potential regulatory genes are known to overlap temporally during elaboration of the multicellular asexual reproductive apparatus (conidiophore) of Aspergillus nidulans. One of these, the stuA (stunted) gene, has been previously classified as a morphological modifier essential for correct spatial organization of the conidiophore. The gene was cloned by complementation of a strain carrying the stuA1 mutation and has been localized to a 5.0 kb KpnI fragment that encodes a 3.3 kb mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
85
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 27 publications
1
85
0
2
Order By: Relevance
“…The process of conidiation has been studied most thoroughly in the filamentous fungus A. nidulans (28)(29)(30). Several key regulatory genes have been identified and cloned and shown to control progression through the various stages of conidiation (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of conidiation has been studied most thoroughly in the filamentous fungus A. nidulans (28)(29)(30). Several key regulatory genes have been identified and cloned and shown to control progression through the various stages of conidiation (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Several key regulatory genes have been identified and cloned and shown to control progression through the various stages of conidiation (28)(29)(30)(31). Properties of the corresponding regulatory proteins and the sites at which some of them act have been determined (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Although StuA is not required for vegetative growth, we found that stuA was transcriptionally activated during the acquisition of developmental competence. Transcriptional activation was induction independent and under the control of unknown genetic loci {Miller et al 1991).…”
mentioning
confidence: 99%
“…Em ensaios de localização celular, a proteína MAS1/GAS2 fusionada a green fluorescent protein -GFP (GAS2::GFP) e foi observada no citoplasma do apressório de M. grisea (Adams et al, 1988). Além disso, a expressão de masA está reprimida em mutante para o fator de transcrição stuA (Twumasi-Boateng et al, 2009), que esta envolvido em um complexo controle genético e morfológico do conidióforo de A. nidulans (Miller et al, 1991).…”
Section: Lista De Abreviaturas E Siglasunclassified
“…Todos os resultados da expressão genica relatica apresentaram significância estatística (p<0,05). (Aguirre et al, 1993;Busby et al, 1996;Miller et al,1991;Sheppard et al, 2005 . O apressório é uma estrutura de função adesiva que auxilia o conídio do fungo fito patogênico a se fixar na superfície da planta.…”
Section: -Tolerância a Ph E Temperaturaunclassified